Pengaruh Kualitas Jasa, Harga dan Citra Perusahaan Terhadap Kepuasan Konsumen (Survei Pada Pasien Instalansi Rawat Inap Kelas III Rumah Sakit PKU Muhammadiyah Yogyakarta) - Dewi Triana (EBBANK, 2019)
Determining the priority of repair or improvement of service quality is needed so that the resources can be allocated well, so as to provide satisfactory service quality for patients. However, appropriate information is needed as consideration and input for the hospital in order to improve the quality of the services. Therefore this study aims to analyze Influence of Service Quality, Price and Image Against Satisfaction of the Third Class In-Patients of PKU Muhammadiyah Yogyakarta Hospital .This research is categorized as verification research and using primary data obtained through interview and questionnaires to 140 patients of PKU Muhammadiyah Hospital of the Third Class. The variables used are service quality, price, image and satisfaction which is reflected by 18 indicators. Path Analysis is used to test the effect of service quality, price and image on patient satisfaction.The results show that Service Quality has positive and significant effect on patient satisfaction. Price has a positive and significant effect on patient satisfaction. The image has a positive and significant effect on patient satisfaction. Where the quality of service has the greatest influence for patient satisfaction.